Glaciology and Glacial Geomorphology - Hagg, Wilfried (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2022)
Why can rigid ice move? How do you measure glacier recession? When was the Little Ice Age? This textbook covers all important aspects of mountain glaciers, from their formation and their importance as water reservoirs to the threat posed by current global warming. Glaciers themselves can also pose a threat to humans and represent a natural hazard in populated mountain areas in the form of ice avalanches and glacial lake outbursts. In addition, however, they are also important landscape formers and have helped to shape large parts of the present-day relief of the Earth, which is one of the classic fields of work of geomorphology and geology. In the individual chapters, the current state of research is presented in a comprehensible manner and illustrated with concise examples, photos and graphics. The book offers a compact introduction for all students of geosciences, curious mountaineers and laymen interested in nature. About the author Wilfried Hagg holds a degree in geography and did his doctorate on the hydrological consequences of glacier retreat in Central Asia. As part of his habilitation and as a Heisenberg Fellow of the German Research Foundation, he has also worked on the nearby mountain glaciers of the Alps and participated in expeditions to mountains in the former Soviet Union, China and New Zealand, as well as to the ice-covered volcanoes of Iceland. Through his university teaching, Wilfried Hagg has experience in imparting geographical knowledge, particularly in the areas of high mountains, glaciology and natural hazards. He currently teaches geography and geology at the Department of Geoinformatics at Munich University of Applied Sciences. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
Introduction and history of research -- Formation of glaciers -- Ice movement. Mass and energy balance of glaciers -- Glacier types and distribution -- Glaciers and climate -- Glaciers and water. and distribution -- Glaciers and climate -- Glaciers and water -- Glacier history -- Glacial hazards -- Glacial erosion -- Glacial accumulation. Accumulation -- Glossary.
Keywords: Geology; Physical geography; Environment; Climatology; Geology; Physical Geography; Environmental Sciences; Climate Sciences